Characteristics of catechin extracted from cocoa husks using microwave assisted extraction (MAE) - DJALAL ROSYIDI; PURWADI; IMAM THOHARI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rahayu PP, Rosyidi D, Purwadi, Thohari I. 2019. Characteristics of catechin extracted from cocoa husks using microwave-assisted extraction (MAE). Biodiversitas 20: 3626-3631. Cocoa husks, a by-product of cocoa processing, were investigated as a source of catechin. The objective of this research was to investigate the best extraction time for catechin of cocoa husk using microwave-assisted extraction (MAE). Four different treatments (4, 6, 8, and 10 min) were tested. Catechin was analyzed using Fourier transform infrared (FTIR) spectroscopy, and total phenol content (TPC) and total catechin content (TCC) were determined by liquid chromatography-mass spectrometry (LC-MS). The longest extraction time (10 min) produced the highest phenolic content, although it was similar to that obtained at 8 min. The IR spectra of the cocoa husk extract were stable for the 4, 6, and 8 min extractions. However, the spectra after the 10 min extraction showed more peaks, especially for phenolic compounds and catechins. The mass spectra of catechin showed a peak at RT 3.11 and a protonated ion peak [M+H]+ at m/z 307. The results for TPC, TCC, FTIR, and LC-MS indicated that a 10 min extraction using MAE was the optimum treatment.